The trial proceedings of the International Criminal Court : ICTY and ICTR precedents - Calvo-Goller, Notburga K. (Martinus Nijhoff Publishers, 2006)
Contains the trial proceedings of the International Criminal Court, the ICTY and the ICTR in one single volume. This book covers the procedural and evidentiary aspects of the trials before the ICC from the beginning of an investigation until the time the convict has served the sentence and it includes ICTY and ICTR precedents.